Identifying Participants Who Would Benefit the Most from an Adult Food-literacy Program - Begley, Andrea; Paynter, E.; Butcher, L.; Bobongie, V.; Dhaliwal, Satvinder (MDPI, 2019)
Food literacy programs aim to improve behaviours required to achieve a quality diet. The objectives of this study were to assess the demographic, food literacy related and dietary behaviour of participants enrolling in Food Sensations® for Adults, a free four-week food literacy program and identify the subgroup of participants who benefit most. Cross-sectional pre-program questionnaire data (n = 1626) from participants enrolling in the program was used to stratify into low, middle and high food-literacy tertiles. Factor scores from a reliability analysis of food literacy behaviours were then used to produce a composite score). Participants were 80.2% female, 56% aged 26 to 45 years and 73.3% from low to middle socio-economic areas. Demographic characteristics were not a significant predictor of the lowest composite food-literacy group. Those with the lowest composite food-literacy tertile score were more likely to have lower self-rated cooking skills, a negative attitude to the cost of healthy foods, lower intakes of fruits and vegetables and a higher frequency of consuming takeaway food and sugary drinks. Food literacy programs must focus on recruiting those who have low self-rated cooking skills, who consider healthy foods expensive and have poor dietary intakes and will most likely to benefit from such programs.